Evaluasi Keterlaksanaan Pembelajaran Tematik dengan Pendekatan Saintifik di Madrasah Ibtidaiyah Al-Hikmah Sintang - Muhartini Muhartini; Tahmid Sabri; Tati Rajati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The aim of this research is to describe the thematic learning evaluation design with a scientific approach at Madrasah Ibtidaiyah Al-Hikmah Sintang. This research was conducted on teachers and students of Madrasah Ibtidaiyah Al-Hikmah Sintang. This research method uses descriptive qualitative. The data collection techniques used were observation, interviews, and documentation. The results of this research are that the design generally has three stages that must be carried out by a teacher, namely the planning stage, the implementation stage and the assessment stage, the implementation of thematic learning is a learning process that is arranged according to what is desired, the assessment process to determine student learning outcomes is through instruments certain things that have been prepared by the government. Obtaining thematic learning results with a scientific approach showed changes in the assessment which were quite good and the average assessment results were above the KKM 78.35. The teacher readiness factor, the teacher has teaching experience. The inhibiting factor is that teachers experience difficulties and are weak in terms of assessment. Student responses were divided into two, namely (a) positive responses, students felt accompanied, and (b) teachers often gave assignments. Teacher responses were divided into two, namely (a) Positive responses: most of the material presented in textbooks and the material taught was easily accepted by students. (b) Negative response: In thematic learning, the teacher still experiences difficulties in terms of assessment. The application of the learning process approach and this approach has the principles of covering, inspiring, strengthening, and providing the background for creating learning methods. Based on the research results, it is recommended that school principals maintain what has been achieved, teachers should increase activities that support learning, students should pay attention to learning.